2005 European Microwave Conference 2005
DOI: 10.1109/eumc.2005.1608854
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-tunable amplifier with a simple tunable admittance inverter

Abstract: This paper proposes a frequency-tunable amplifier with a simple frequency-tunable admittance inverter. The admittance inverter consists of a fixed-length transmission-line and only a single shunt variable capacitor connected in the midst of the line. The inverter can maintain the 90-degree phase-shift property while tuning its operating frequency, and is suitable for a general-purpose circuit section for frequency-tunable RF circuits. The fabricated tunable amplifier employs the inverter as a matching circuit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…L-band frequency tunable amplifier using the varactor [1], Xband frequency tunable low noise amplifier (LNA) using tunable filter [2], tunable LNA for 3.1 to 10 GHz ultra wide band system [3] are examples for the frequency tunable amplifiers. Frequency tunable amplifiers in more higher frequency band at Ku-band [4,5] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…L-band frequency tunable amplifier using the varactor [1], Xband frequency tunable low noise amplifier (LNA) using tunable filter [2], tunable LNA for 3.1 to 10 GHz ultra wide band system [3] are examples for the frequency tunable amplifiers. Frequency tunable amplifiers in more higher frequency band at Ku-band [4,5] have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, a lot of research has reported multiband=multimode and reconfigurable RF systems such as tunable antennas, filters, power amplifiers, and matching networks. [1][2][3][4][5][6][7][8] In these systems, tunable capacitors are a key component. RF-MEMS tunable capacitors are more suitable for these systems than any other devices such as p-i-n diodes, silicon-on-insulator (SOI) switches, [9][10][11] or barium-strontium-titanate (BST) type tunable capacitors, 12) thanks to their low loss and excellent linearity.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, the impact of using tunable matching networks on amplifier efficiency and linearity has not been investigated previously. Although there are many tunable matching network designs, [2,15,25,28,32,33,35,38,39] examples of complete tunable amplifier modules are not many [6,8,11,18,37]. Most of the tunable amplifiers presented in the literature are designed for frequencies between 10-40 GHz and provide up to 10% tunability.…”
Section: Introductionmentioning
confidence: 99%
“…This frequency band of operation and range of tunability is insufficient for the realization of the commercial SDR concept. Furthermore, no information was supplied in [6,8,11,18,37] regarding the efficiency and linearity of these tunable amplifiers. However, it is widely accepted that the linearity and efficiency of RF front-end components are bottlenecks in reconfigurable radio design [16,36].…”
Section: Introductionmentioning
confidence: 99%